Impact of biometric characteristics of udder and teats on milk quality of indigenous dairy cattle - Singh, Navav; Sharma, Sanjita; Sharma, Vishnu; Sharma, Amit; Dhakad, Govind Singh (Indian Journal of Dairy Science, 2022)
The present investigation was carried out to investigate the effect of biometric characteristics of udder and teats with milk Somatic Cell Count which are important for farmers, manufacturers and consumers. For this study we collected 50 ml milk from 150 Indigenous lactating cattle breeds viz., Kankrej, Sahiwal and Rathi cattle (50 from each breed) reared under similar management conditions at university cattle farms located in Bikaner city of Rajasthan, India.Â  Udder and teat morphometric parameters, i.e. Normal and pendulous shape of the udder, depth of udder, flat, inverted and pointed shape of teat-end, length of teats were measured before milking. We observed the significant (P